Lack of Communication, Loneliness and Uprooting in La mujer que cayó del cielo by Víctor Hugo Rascón Banda - Gidi Blanchet, Claudia Elisa (2025)
La mujer que cayó del cielo, by the Mexican playwright Víctor Hugo Rascón Banda, is a play that recreates an event that occurred in the 1980s in the United States: the forced and unjustified confinement of a Tarahumara woman in a psychiatric hospital, caused by lack of knowledge of the marginal language she spoke. This article analyzes how the author, although starting from an individual case of migration motivated by personal issues, manages to create a work of art that represents a human and social problem of great significance: migration, discrimination, and absolute isolation. To describe the conflictive contact between groups in unequal conditions of domination and subordination, the notion of migrant subject proposed by Antonio Cornejo Polar is used.